442. Clinical Outcomes of Checkpoint Inhibitor Therapy in People with HIV: A Single-Center Case Series. (15th December 2022) - Sans, Hannah M; Jones, Benjamin; Isaza, Erin; Chin-Hong, Peter V; Henrich, Timothy J; Peluso, Michael J
Abstract: Background: Immunotherapeutics, particularly immune-checkpoint inhibitors (ICI), have transformed the treatment landscape for advanced cancer. Such therapies could considerably benefit people with HIV (PWH), yet PWH have often been excluded from ICI trials such that data regarding ICI safety in PWH are limited. In addition, ICIs have recently been proposed as latency reversing agents that could impact the HIV reservoir. Here, we report the outcomes in a cohort of PWH after ICI therapy. Methods: Using the electronic health record, we systematically identified all PWH with advanced cancer who received ICIs from January 2000 to December 2018 at one academic medical center. We collected data on demographics, HIV history, and HIV and hematologic parameters before and after ICI in 25 PWH over 29 treatment episodes. We cataloged adverse events following treatment. Results: In this cohort, ICI therapy was not associated with a significant increase in plasma HIV RNA levels nor with significant change in CD4 + T-cell count, CD8 + T-cell count, or CD4/CD8 ratio (Figure 1). Among 19 treatment episodes with available pre- and post- treatment data, there were five viral blips (26%); HIV RNA exceeded 200 copies/mL in one episode. The blip rate observed among PWH on ART in the literature ranges from 10-30% and among PWH receiving ICI from 0-33%. Adverse events included infectious and autoimmune conditions across multiple organ systems including systemic, pulmonary, gastrointestinal/hepatic, genitourinary, neurologic, endocrine, and dermatologic. The most common adverse events were diarrhea (n=7) and rash (n=5). Five deaths occurred within one month of ICI initiation; all were attributed to progressive malignancy. Figure 1: Changes in HIV parameters associated with checkpoint inhibitor therapy (a) Pretreatment plasma HIV RNA, n=23. There was one episode in which the pretreatment plasma HIV RNA was greater than 200 copies/ml. (b) Pretreatment CD4+ Tcell counts, n=24. (c) Longitudinal plasma HIV RNA trends in 5 individuals who experienced a viral blip, defined as an increase in plasma HIV RNA from "not detected" to "detected" or greater within a year of ICI initiation. Symbols represent unique participants. (d) Pretreatment and posttreatment plasma HIV RNA values closest to ICI initiation, n=19. Points are scaled to proportion of sample. (e) Pretreatment and posttreatment CD4+ T-cell counts closest to ICI initiation, n=20. Thick line represents the change in median M between the two time points. (f) Pretreatment and posttreatment CD4+ T-cell percentages closest to ICI initiation, n=19.Thick line represents the change in median M between the two time points. (g) Pretreatment and posttreatment CD8+ T-cell counts closest to ICI initiation, n=18. Thick line represents change in median M between the two time points. (h) Pretreatment and posttreatment CD4/CD8 ratios closest to ICI initiation, n=18. Thick line represents the change in median M between the two time points. Conclusion: This single-center cohort demonstrated no significant impact on HIV parameters among PWH receiving ICI. This study contributes to the growing body of evidence suggesting the safety and tolerability of ICI in PWH in both HIV and non-HIV-related outcomes and supports the inclusion of PWH in future ICI clinical trials. While we did not see an increased rate of viral blips on routine clinical testing, our findings also provide key preliminary data supporting the safety and tolerability of ICIs in future studies of these agents as HIV therapeutics, for example as agents that may reverse HIV latency. Disclosures: All Authors : No reported disclosures.